Twelve steps to normal - Penn, Farrah (2018)
Upon returning from a year in Oregon to Texas and her alcoholic father, Kira is distressed to find three of her father's rehab friends staying at her home, while her own friends seem distant.--Provided by Publisher.
"James Patterson presents"--Jacket.
Keywords: Alcoholism -- Fiction; Fathers and daughters -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Single-parent families -- Fiction; Grief -- Fiction; Alcoholism -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Single-parent families -- Juvenile fiction; Grief -- Juvenile fiction; Young adult fiction